Ler a vida e se ler a partir de uma obra paradidática: um projeto de educação linguística crítica envolvendo os temas gênero, sexualidade, raça e arranjos familiares com estudantes da educação básica - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This study analyzes an action research (THIOLLENT, 2006, 2011) conducted by a professor and academic researcher who sought to problematize issues addressed by a paradidatic book, with students in the last year of elementary school, in a rural town of Goiás. Its main objective is to problematize themes of gender, sexuality, race and family arrangements, through reading the lives of students and the paradidactic book “Vento forte, de sul e norte”, by Manuel Filho, generated within an institutional reading project based on critical language education. Such problematizations are raised based on the themes of race (QUIJANO, 2005, FERNANDES, 2008; NASCIMENTO; FONSECA, 2013), gender and sexuality (WEEKS, 2019; LOURO, 2019; DANTAS, 2010; CUGINI, 2020) and family arrangements (FACO; MELCHIORI, 2009; CAETANO et al, 2016; BIROLI, 2014; LACERDA, 2006). The academic praxiologies that conduct this research are supported by critical approaches to applied linguistics (MOITA LOPES, 2003/ 2006/ 2009; KUMARAVADIVIVELU, 2006; RAJAGOPALAN, 2003, 2006; KLEIMAN, 2013; PENNYCOOK, 2006/ 1998; FRANK, 2021; OLIVEIRA, 2014, 2016, 2021), critical pedagogy (FREIRE, 2021a/ 2021b; hooks, 2017) and critical reading and critical reading training (CORADIM, 2008; BRAHIM, 2007). The methodological support is action research (THIOLLENT, 2006, 2011) which took place from a reading project entitled: Learning to be Junco. The empirical material produced derives from the meetings of the reading project with interactions recorded in audio, written activities of problematization on the themes and reading sheets of the paradidatic book constructed by the participants of the research. The results indicate that the maintenance of hegemonic powers are continuously present in social relationships, especially at school and in family and religious institutions. However, the problematizations on themes of racial, gender, sexual and family diversity generated in the participants points of reflection about their actions, which may (or may not) contribute to the destructuring of dominating practices, through language.
Reading life and reading oneself from a paradidatic book: a critical linguistic education project involving gender, sexuality, race and family arrangements with basic education students
Keywords: Educação linguística crítica; Raça; Gênero e sexualidade; Leitura paradidática - Arranjos familiares; Critical linguistic education; Race; Gender and sexuality; Paradidatic reading - Family arrangements; CIENCIAS HUMANAS::EDUCACAO; LINGUISTICA::TEORIA E ANALISE LINGUISTICA